Atypical porcine pestivirus—A widespread virus in the Swedish wild boar population. Issue 4 (11th August 2021) - Stenberg, Hedvig; Leveringhaus, Elena; Malmsten, Anna; Dalin, Anne‐Marie; Postel, Alexander; Malmberg, Maja
Abstract: The recently identified causative agent of congenital tremor in domestic piglets, atypical porcine pestivirus (APPV), was detected in serum from Swedish wild boar. A previous study from Sweden described APPV in domestic piglets suffering from congenital tremor, but the APPV situation in the wild boar population was unknown. In this study, 595 serum samples from wild boar originating from 13 counties in the south and central parts of Sweden, collected between 2000 and 2018, were analysed for the presence of the APPV‐genome and for antibodies against the APPV‐glycoprotein E rns . The results revealed that APPV is highly abundant in the Swedish wild boar population; 12% (73/595) were APPV‐genome positive in serum and 72% (433/595) of the tested wild boars displayed APPV‐specific antibodies. The present study also shows that APPV has been present in the Swedish wild boar population since at least the year 2000. The viral sequences obtained from the wild boars were highly similar to those obtained from Swedish domestic pigs positive for APPV and suffering from congenital tremor, suggesting a viral exchange between wild boars and domestic pigs. The high proportion of viraemic and seropositive wild boar is indicative of wild boar being an important reservoir for APPV.